Pengaruh Corporate Social Responsibility pada Brand loyalty di Mediasi oleh Brand reputation dan Customer satisfaction pada Brand Wardah - Nadia Nurrahmah Sari; Henny Welsa; Nonik Kusuma Ningrum (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
This study aims to investigate the impact of Corporate Social Responsibility (CSR) on Brand loyalty mediated by brand reputation and Customer satisfaction for the Wardah brand. The research employs a quantitative approach, involving 150 Wardah consumers as samples. Data was collected using a Likert scale with a score range of 1-5 through an online questionnaire distributed via Google Form. The results of the study indicate that: (1) CSR has a positive and significant effect on brand reputation, (2) CSR does not have a significant effect on Customer satisfaction, (3) brand reputation has a positive and significant effect on Brand loyalty, (4) Customer satisfaction has a positive and significant effect on Brand loyalty, (5) CSR does not have a significant effect on Brand loyalty, (6) there is an effect of CSR on Brand loyalty through brand reputation, and (7) CSR does not have a significant effect on Brand loyalty mediated by Customer satisfaction.